Potensi Makanan Tradisional Awetan Suku Melayu Kabupaten Kayong Utara sebagai Sumber Belajar Biologi - Reza Fahrazi; Mahwar Qurbaniah; Anandita Eka Setiadi (SAP (Susunan Artikel Pendidikan), 2023)
The Malay people of North Kayong Regency have traditional preserved foods that have been passed down from generation to generation. Preserved traditional food is a local potential that can be used as a learning resource for meaningful learning. This research aims to analyse the potential of traditional foods used as biology learning resources. This research used a qualitative descriptive approach with an exploratory method. Data collection were from observation, identification, direct communication, indirect communication and documentation techniques. The results of the research showed that there were 19 types of preserved traditional food from the Malay tribe of North Kayong Regency, namely dried bamboo shoots, bamboo shoots, dodol pumpkin, lempok durian, tempoyak, cengkarok tape, coconut mesekat, smoked fish, salted fish, pedak bloat, anchovies, amplang, shrimp. dried, cencalok, Belacan, Pekasam Pempapahat, Pekasam clams, and dried squid. The results of the identification showed that the types of plants and animals that were processed into traditional preserved foods include: bamboo, peringgi pumpkin, durian, cassava, black sticky rice, coconut, mackerel fish, sengat fish, durian fish, gelame fish, pempirang fish, mackerel fish , mayung fish, stingrays, sungkur shrimp, scallops, clams, squid and anchovies. The potential of preserved traditional food was in accordance with biology learning material on the classification of living things, addictive substances, biodiversity and biotechnology. It was concluded that the preserved traditional food of the Malay Tribe of North Kayong Regency had the potential as a biology learning resource of 93.2% (very good category).